(untitled) (Web of Teachers: Inderscience Research, 2024)
Caring for health and strengthening it is a natural need of a cultured person, an integral element of his life. Health is a complex and at the same time holistic, multidimensional dynamic state that develops in the process of realizing genetic potential in a specific social and economic environment and allows a person to perform his biological and social functions to varying degrees. According to the World Health Organization, health is a state of complete physical, mental and social well-being, and not merely the absence of disease or infirmity.